A bibliographical and historical study of left radical movements and some alleged left radical movements in South Africa and Namibia, 1900-1981 - Bohmer, Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Bibl.) -- University of Stellenbosch, 1984.